Bibliometric insights into Schizophrenia and genetic variation - Azman, Norainin Sofiya; Abd. Rahim, Nour El Huda; Mat Rasid, Siti Norain; A.Talib, Norlelawati; Abdull Jalil, Mohd Asyraf; Md Rosli, Ahmad Nabil (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Schizophrenia is a severe psychiatric disorder that is known for its complexity as well as involves genetic variation. The aim of this study was to explore the trend in the field of genetic variation-related research in schizophrenia from a bibliometric perspective. Materials and methods: Research articles on schizophrenia and genetic variation-related research were obtained from the Scopus database from its inception to October 20, 2023. The search strategy was set as the following using the search terms "Schizophrenia", "genetic variation", “snp” and “cnv”. Original articles, reviews, and proceedings were included in the analysis. Using filters, only English articles were selected and used for further analysis. R packages “Bibliometrix” and “Biblioshiny” were used to summarize the main findings, count the occurrences of the top keywords, visualize the collaboration network between countries, and generate a three-field plot. VOSviewer software was applied to conduct keyword co-occurrence analyses. Results: A total of 403 publications on schizophrenia and genetic variation were included. Publications were mainly from the USA, UK, and China. The highest number of publications was found in a list of relevant journals. Apart from “schizophrenia” and “genetic variation”, the terms “bipolar disorder,” “autism,” and “GWAS” were also the most frequently used keywords. Conclusions: Over the past 17 years, this bibliometric analysis has mapped out an important knowledge structure consisting of countries, institutions, authors, journals, and articles in the research field of schizophrenia and genetic variation. The findings provide not only a comprehensive perspective on the wider landscape of this research topic but also pave the way for potential precision medicine approaches, enabling more targeted therapeutic interventions based on individual genetic profiles.